Drug repurposing in the context of common bacterial patho- gens: insights from an in vitro study - Donadu, Matthew Gavino; Zanetti, Stefania; Battah, Basem; Hetta, Helal F.; Matusovits, Danica; Kárpáti, Krisztina; Finta, Virág; Csontos, Berta; Kuklis, Anna; Szikora, Fruzsina; Csegény, Adrienn; Szalma, Lea; et al. (Acta Biologica Szegediensis, 2023)
The clinical problem of multidrug resistance (MDR) in bacteria is due to the lack of novel antibiotics in development and the dwindling pipeline of drugs receiving market authorization. Repurposing of non-antibiotic pharmacological agents may be an attractive pathway to provide new antimicrobial drugs. The aim of the present study was to ascertain the antibacterial and adjuvant properties of a wide range of pharmaceuticals against antibiotic-susceptible and drug-resistant bacteria. Sixty-five (n = 65) pharmacological agents were included in our experiments. For Gram-positive bacteria, Staphylococcus aureus ATCC 43300 (methicillin-resistant), S. epidermidis ATCC 12228, Streptococcus pyogenes ATCC 12384 and Enterococcus faecalis ATCC 29212 were used, while for Gram-negative bacteria, Enterobacter cloacae ATCC 13047 (extended-spectrum β-lactamase-positive), Klebsiella pneumoniae ATCC 49619, Serratia marcescens ATCC 29632 and Pseudomonas aeruginosa ATCC 27853 were included as representative strains. The minimum inhibitory concentrations (MICs) of the tested compounds were determined using the standard broth microdilution method, while a MIC reduction assay was included to ascertain the effect of the tested compounds on the MICs of standard antibiotics (ceftriaxone, ciprofloxacin and gentamicin). Seventeen and twelve drug molecules tested showed measurable antibacterial activities (MIC: 32-512 µg/mL) against Gram-positive and Gram-negative bacteria, respectively. Several compounds decreased the MICs of ciprofloxacin and gentamicin. Although there are increasing number of studies in this field, there are still significant gaps in the evidence to the potential use of non-antibiotic drugs in antimicrobial drug repurposing.